VD_FINDINFO Jug / 2015 / 284 vom 27. März 2015 - VD Tribunal cantonal (2015)
DROIT DE LA FONCTION PUBLIQUE, EMPLOYÉ PUBLIC, RÉPRIMANDE, RÉSILIATION ABUSIVE, PROPORTIONNALITÉ, TORT MORAL | 5 al. 2 Cst., 14 LPers-VD, 16 al. 1 LPers-VD, 16 al. 3 LPers-VD, 5 al. 3 LPers-VD, 50 LPers-VD, 59 LPers-VD, 135 RLPers-VD, 7 al. 1 RLPers-VD